Women's satisfaction with the birthing experience in relation to duration of labour, obstetric interventions and mode of birth. (March 2020) - Kempe, Per; Vikström-Bolin, Marie
Highlights: We studied the effects of the duration of labour and obstetric interventions on maternal satisfaction with labour and birth in TGCS Group 1. NVB, no oxytocin augmentation, no epidural anaesthesia and shorter labour were significantly related to a higher satisfaction score. In a multiple regression analysis, duration of labour and mode of birth had independent significant effects on the satisfaction score. We conclude that the prevention of long labour is important to improve women's satisfaction with birth. Abstract: Objective: To study the influence of the duration of labour on women's satisfaction with their birthing experience. Study design: All labours and births during a four-year period at a secondary level Hospital were included in a continuous audit of events and outcomes based on the Ten Group Classification System (TGCS). The women scored their overall satisfaction with their birth experience on an ordinal Visual Analog Scale. Results: 1780 nulliparous women with a cephalic fetus at term and spontaneous onset of labour in TGCS Group 1 gave birth during the study period. 1716 had complete data on duration of labour and, of these, 1380 (80, 4 %) rated their satisfaction with their birthing experience. Satisfaction with the birthing experience was significantly related to mode of birth, oxytocin augmentation, epidural anaesthesia and to duration of labour. Duration of labour and mode of birth had independent significant statistical effect on the satisfaction with the birthing experience. Conclusion: Although various aspects of labour management are associated with a negative birth experience, the effect of prolonged labour is independently significant and measures taken to avoid prolonged labour could result in a net benefit to the woman's satisfaction.